2019
DOI: 10.1186/s13256-019-2090-z
|View full text |Cite
|
Sign up to set email alerts
|

Renal pyelocalyceal squamous cell carcinoma in a patient with an ectopic kidney presenting with chronic pyelonephritis: a case report

Abstract: Background Until now, few cases of pelvis squamous cell carcinoma in various renal anomalies have been reported. To our knowledge, primary squamous cell carcinoma arising from a pelvic ectopic kidney has never been described. In this report, we describe a case of renal pyelocalyceal squamous cell carcinoma in a patient with an ectopic kidney presenting with chronic pyelonephritis. Case summary A 73-year-old Caucasian woman presented to our hospital with pyelonephritis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Renal squamous cell carcinoma is rare and is associated with chronic inflammation due to renal stones or chronic infection. There have been only 2 previous reports of 3 cases of xanthogranulomatous pyelonephritis with renal squamous cell carcinoma (14,18). In this report, the patient presented similar clinical manifestations as those in previous reports (14,18,36), including initial symptoms of urinary infection (fever, low back pain), elevated peripheral blood white blood cell and neutrophil counts with moderate anemia, elevated CRP, and urine white blood cells and occult blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal squamous cell carcinoma is rare and is associated with chronic inflammation due to renal stones or chronic infection. There have been only 2 previous reports of 3 cases of xanthogranulomatous pyelonephritis with renal squamous cell carcinoma (14,18). In this report, the patient presented similar clinical manifestations as those in previous reports (14,18,36), including initial symptoms of urinary infection (fever, low back pain), elevated peripheral blood white blood cell and neutrophil counts with moderate anemia, elevated CRP, and urine white blood cells and occult blood.…”
Section: Discussionmentioning
confidence: 99%
“…There have been only 2 previous reports of 3 cases of xanthogranulomatous pyelonephritis with renal squamous cell carcinoma (14,18). In this report, the patient presented similar clinical manifestations as those in previous reports (14,18,36), including initial symptoms of urinary infection (fever, low back pain), elevated peripheral blood white blood cell and neutrophil counts with moderate anemia, elevated CRP, and urine white blood cells and occult blood. After surgery, the clinical symptoms disappeared, and blood test results, urine analysis results, and CRP level returned to normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stage, the clinical manifestation of renal SCC is nonspecific. It has been reported that most cases of SCC of the renal pelvis present with hydronephrosis, chronic pyelonephritis, kidney stones, and renal cysts [2,[6][7][8]. SCC cases also have been discovered in the kidneys with various anomalies such as horseshoe kidney, ectopic kidney, polycystic kidney disease, and renal calyceal diverticulum [2].…”
Section: Discussionmentioning
confidence: 99%